PHYTOCHEMICAL ANALYSIS OF ETHANOLIC EXTRACT OF LEAVES OF LEUCAS INDICA (EELLI) - CHANDRASHEKAR. R; RAO S.N. (International Journal of Pharma and Bio Sciences, 2013)
Plants of genus Leucas belongs to family Lamiacae and have been widely employed by the traditional healers to cure many diseases. The objective of the study was to do preliminary phytochemical screening of Ethanolic Extract of Leaves of Leucas indica (EELLI). About 1000 gm of air dried powdered material of leaves of Leucas indica was extracted with 90% ethanol in a soxhlet extractor for 36 hours. It was concentrated to dryness under reduced pressure and controlled temperature (40-50oC) using rotary evaporator. The ethanolic extract yielded a dark brown Sticky mass weighing 125g. The ethanolic extract was concentrated by vacuum distillation to dryness; the yield obtained was 12.5% w/w with respect to dried leaf. The preliminary phytochemical screenings of EELLI for its phytochemical constituents were performed using generally accepted laboratory technique for qualitative determinations. Preliminary phytochemical screening of EELLI shows the presence of phytosterols, triterpenoids, flavinoids, lactones, glycosides, fatty acids, phenolic compounds and tannins.